2019
DOI: 10.1021/acs.est.9b01983
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Nanoscale and Ionic Cu and Zn during the Incineration of Digested Sewage Sludge (Biosolids)

Abstract: Engineered nanoparticles (NP) discharged to sewers are efficiently retained by wastewater treatment plants and accumulate in the sewage sludge, which is commonly digested. The resulting biosolids are either used as fertilizer or incinerated. In this study, we address the transformation of Cu and Zn during sewage sludge incineration and evaluate whether the form of Cu or Zn (nanoparticulate versus dissolved) added to the digested sewage sludge affects the fate of the metals during incineration. We spiked CuO-NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…LCF to bulk-EXAFS on the same samples indicated that SLG AQ can be described by 80% Cu x S (amorphous) and 20% chalcopyrite ( Table 2). 29 For SLG NP, identical analyses returned a similar fraction of Cu x S (81%), but in addition to chalcopyrite (11%) a comparable fraction (8%) was associated with Cu(II)-O references (tenorite and copper sulphate). 29 To compare the integrated LCF fractions determined from the spatially resolved XAS data with the fractions derived from bulk EXAFS LCF, the spatially resolved XAS data were weighted with the intensity difference between the pre-and post-edge (DI i ).…”
Section: The Spatial Distribution Of the Cu Speciation In Sludge Sampmentioning
confidence: 86%
See 3 more Smart Citations
“…LCF to bulk-EXAFS on the same samples indicated that SLG AQ can be described by 80% Cu x S (amorphous) and 20% chalcopyrite ( Table 2). 29 For SLG NP, identical analyses returned a similar fraction of Cu x S (81%), but in addition to chalcopyrite (11%) a comparable fraction (8%) was associated with Cu(II)-O references (tenorite and copper sulphate). 29 To compare the integrated LCF fractions determined from the spatially resolved XAS data with the fractions derived from bulk EXAFS LCF, the spatially resolved XAS data were weighted with the intensity difference between the pre-and post-edge (DI i ).…”
Section: The Spatial Distribution Of the Cu Speciation In Sludge Sampmentioning
confidence: 86%
“…The sludge was dewatered, dried at 105 C and incinerated in a pilot scale bubbling bed type uidized bed reactor resulting in the ashes ASH NP from SLG NP and ASH AQ from SLG AQ. A detailed description of the samples and their generation can be found in Wielinski et al 29 The samples SLG NP, SLG AQ, ASH NP and ASH AQ correspond to D-NP, D-AQ, D-NP-ap and D-AQ-ap, in Wielinski et al 29 The sludge and ash samples (ASH NP and ASH AQ) were dried, embedded into an epoxy resin (one part EpoFix Hardener and seven parts EpoFix Resin, both Struers) at 180 mbar (Citovac, Struers), allowed to harden for 24 h, cut into thin sections (d ¼ 30 mm) and mounted on 1 Â 1 cm 2 pre-cut 250 mm-thick Si Wafers (TED PELLA, Inc.). Bulk Cu concentrations were determined using inductively coupled plasma mass spectrometry (ICP-MS, 7500cx, Agilent Technologies, Inc.) aer acid digestion of 10 to 20 mg of sample (2 mL H 2 O 2 and 9 mL aqua regia for the sludge samples or 9 mL HNO 3 and 200 mL HF for the ash samples) in a microwave system (ETHOS 1, MLS GmbH) for the sludge samples and in an ultraclave (MLS GmbH) for the ash samples.…”
Section: Sample Preparation and Characterization Of Experimental Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, NMs used for biocidal applications in household products and release “down the drain” will experience strong reducing conditions in the sewage network and in wastewater treatment plants. Under these conditions, Ag NMs have been widely demonstrated to transform into silver sulfide [ 31–33 ] and similar transformation reactions have been shown for CuO NMs, resulting in the formation of Cu 2 S. [ 34 ] For ZnO, more complex speciation changes have been proposed, although changes are likely to be dominated by sulfidization to ZnS, while under certain conditions the development of phosphatized forms can occur. [ 35,36 ] Fate and transport, exposure modelling, and indeed work on NM hazard, needs to recognize that for some materials (e.g., Ag, Cu, CuO, ZnO), fully or partially chemically transformed NMs will be the main form released in effluent and sewage sludge rather than their pristine chemistry.…”
Section: Key Nm Environmental Transformations Processesmentioning
confidence: 96%